Embryo quality is the main factor affecting cumulative live birth rate after elective single embryo transfer in fresh stimulation cycles. (November 2015) - Niinimäki, Maarit; Veleva, Zdravka; Martikainen, Hannu
Abstract: Objective: The study was aimed to evaluate which factors affect the cumulative live birth rate after elective single embryo transfer in women younger than 36 years. Additionally, number of children in women with more than one delivery per ovum pick-up after fresh elective single embryo transfer and subsequent frozen embryo transfers was assessed. Study design: Retrospective cohort study analysing data of a university hospital's infertility clinic in 2001–2010. A total of 739 IVF/ICSI cycles with elective single embryo transfer were included. Analyses were made per ovum pick-up including fresh and subsequent frozen embryo transfers. Factors affecting cumulative live birth rates were examined in uni- and multivariate analyses. A secondary endpoint was the number of children born after all treatments. Results: In the fresh cycles, the live birth rate was 29.2% and the cumulative live birth rate was 51.3%, with a twin rate of 3.4%. In the multivariate analysis, having two (odds ratio (OR) 1.73; 95% confidence interval (CI) 1.12–2.67) or ≥3 top embryos (OR 2.66; 95% CI 1.79–3.95) was associated with higher odds for live birth after fresh and frozen embryo cycles. Age, body mass index, duration of infertility, diagnosis or total gonadotropin dose were not associated with the cumulative live birth rate. In cycles with one top embryo, the cumulative live birth rate was 40.2%, whereas it was 64.1% in those with at least three top embryos. Of women who had a live birth in the fresh cycle, 20.4% had more than one child after all frozen embryo transfers. Among women with three or more top embryos after ovum pick-up, 16.1% gave birth to more than one child. Conclusion: The cumulative live birth rate in this age group varies from 40% to 64% and is dependent on the quality of embryos. Women with three or more top embryos have good chance of having more than one child per ovum pick-up without elevated risk of multiple pregnancies.